Strategi Biro Pemberitaan Parlemen DPR RI Menghadapi Berita Negatif di Media Massa - Yonarisman Muhammad Akbar; Raesita Rakhmawati Rosadi; Ida Royandiah; Mohamad Fajar Haqi Ismaya; Dina Fadiyah (Madani: Jurnal Politik dan Sosial Kemasyarakatan, 2023)
The House of Representatives of the Republic of Indonesia (DPR RI) plays a vital role and significant contribution in the areas of legislation, budgeting, and oversight. This institution is known as the "house of the people" as it serves as a place for representatives to channel the aspirations of the public. However, various recent data indicates that the image of this representative institution tends to be negative. DPR RI often receives unfavorable media coverage, ranging from performance issues to problems such as members' absence from sessions. There is a significant challenge for this institution to convince the public to have a high and dominant perception of it in a positive light. The Parliament News Bureau holds the role of public relations, being at the forefront of providing information and disseminating positive news about DPR RI's performance. This research focuses on the strategies employed by the Parliament News Bureau in handling negative news about the DPR RI in the mass media. The study is a qualitative research with descriptive analysis. Data is gathered from in-depth interviews with the Head of the Parliament News Bureau, documents, and literature studies. The results of this research show that the Parliament News Bureau focuses on generating positive news and disseminating it through various mass media channels and digital platforms such as television, radio, and social media. Additionally, the Parliament News Bureau continuously monitors the mass media to stay updated on news related to the institution and its members.